Ответы 2

  • x^3-6x^2-7x=0

    x(x^2-6x-7)=0

    x=0

     x^2-6x-7=0  

    d=b^2-4ac=36-4*(-7)=64

     x1=(6+8)/2=7

    x2=-2/2=-1 

    Ответ:-1;0;7. 

  • x^{3}=6x^{2}+7x\\ x^{3}-6x^{2}-7x=0\\ x(x^{2}-6x-7)=0\\ x=0\ x^{2}-6x-7=0\\ \ D_1=9+7=16>0\\ \ x_1,2=\frac{3±\sqrt{16}}{1}\\ \ x_1=3+4=7\\ \ x_2=3-4=-1\\

    Ответ: x=0; x=7; x=-1

    • Автор:

      scott28
    • 5 лет назад
    • 0
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years